SUBSTITUTION OF SOYBEAN MEAL WITH INDIGOFERA LEAF FLOUR (Indigofera sp.) IN GROWING FEED OF STRIPED CATFISH (Pangasianodon hypophthalmus) - Setiyowati, Evi Dwi; Hudaidah, Siti; Ediwarman, Ediwarman; Panigoro, Novita; Santoso, Limin (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
Soybean meal is one of the feed ingredients that is still imported, so indigofera leaf flour is tried as an alternative to local feed ingredients to reduce feed costs. The purpose of this study was to determine the effect of indigofera leaf flour (Indigofera sp.) as a substitute for soybean meal on growth performance on enlargement of striped catfish (Pangasianodon hypophthalmus). This study used a completely randomized design with 4 treatments and 3 replications. P1 (without substitution of indigofera leaf flour), P2 (substitution of soybean meal with 10% indigofera leaf flour), P3 (substitution of soybean meal with 20% indigofera leaf flour), P4 (substitution of soybean meal with 30% indigofera leaf flour). The data obtained were analyzed using analysis of variance (ANOVA) and further tested with Duncan's test. Based on statistical analysis, the test feeding had a significant effect (p<0.1) on absolute weight growth, specific growth rate, and feed efficiency and the yield was not significantly different (p>0.1) on absolute length and survival rate of fish. The results showed that the use of indigofera leaf flour as a substitute for soybean meal up to a limit of 20% was able to provide a relatively better growth performance than 30%.